Дослідження особливостей використання баз даних NoSQL для великих даних і веб-додатків - Вихрист, О. В. (ХНУРЕ, 2023)
In response to the limitations of traditional relational databases, which struggle to adapt to today's data-intensive applications, many companies are turning to NoSQL databases. These alternatives offer a number of advantages, including scalability, flexibility, performance, and cost-effectiveness, making them an ideal choice for processing large volumes of unstructured data. Although NoSQL databases are not standardized and have certain limitations, the benefits they provide are often too great to ignore for many use cases